Role of particles and lattice rotation in tension–compression asymmetry of aluminium alloys. (December 2022) - Sun, Fengwei; Wang, Shengxun; Xie, Qingge
Abstract: Plastic deformation of aluminium alloy AA6061 under tension and compression is investigated using a strain gradient crystal plasticity model implemented with the finite element method. This approach takes into account the microstructure as determined experimentally by electron backscatter diffraction (EBSD). The asymmetry of stress strain curves in loading of tension and compression (TC) is revealed for the FCC crystal structure. Plastic slip on activated slip systems leads to lattice rotation of crystal matrix and particles towards specific orientations, resulting in variation of moduli. The evolution of two different types of dislocations, statistically stored dislocations (SSD) and geometrically necessary dislocations (GND), is investigated to reveal the TC asymmetry due to slip resistance. It is found that the TC asymmetry at the yield strain is caused by lattice rotation of both crystal matrix and particles. When strain increases, the TC asymmetry is due to a combination of lattice rotation of crystal matrix and particle and variation of the GND density. As particle content increases, the TC asymmetry is mainly attributed to lattice rotation of particles at large strain. Highlights: Tension/Compression (TC) of Al alloy was analysed with a crystal plasticity model. Lattice rotation of particles makes a significant contribution to the TC asymmetry. Compression leads to high GND density and rotation towards low-modulus orientation.